Chromatic dispersion penalties in orthogonal subcarrier - Optical tandem single sideband systems (OTSSB) - Abdul-Rashid, , HA; Lanka, , SK; Lee, , RC; Tayahi, , MB; Al-Qdah, , MT; Chuah, , HT (2005)
This paper deals with dispersion penalties in an Optical Tandem Single Sideband system using orthogonal subcarriers. A mathematical model demonstrates the phase imbalance of the upper and lower sideband caused by chromatic dispersion and verified by simulations. The transmission over 10km of single mode fiber (SMF) using different subcarrier frequencies shows higher penalties for higher subcarrier frequencies.